2017
DOI: 10.1177/0972150916666966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eWOM Valence on Online Retail Sales

Abstract: Online retail sector in India has witnessed a phenomenal growth in recent times. Online shopping has also become a popular trend among the younger generation in India. Increasing number of shoppers visit online retailer websites and read online reviews before making their purchase decision. The online reviews or electronic word of mouth (eWOM) becomes an important guiding tool for the online shoppers with its intrinsic product information and evaluation characteristics. The present study aims to analyze the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 46 publications
(64 reference statements)
2
36
0
2
Order By: Relevance
“…Users feel less confident and threatened with online stores because two-way communication does not exist, and they depend solely on the eWOM. Therefore, eWOM becomes an important guiding tool for online shoppers to shop online (Roy, Datta & Basu 2017). Kim, Ferrin and Rao (2008) examined how trust and risks influence the purchasing decisions of internet users, and it is concluded that among the variables reviewed, perceived risk and website information have a strong impact on purchase decisions.…”
Section: Relationship Between Opr and Opimentioning
confidence: 99%
“…Users feel less confident and threatened with online stores because two-way communication does not exist, and they depend solely on the eWOM. Therefore, eWOM becomes an important guiding tool for online shoppers to shop online (Roy, Datta & Basu 2017). Kim, Ferrin and Rao (2008) examined how trust and risks influence the purchasing decisions of internet users, and it is concluded that among the variables reviewed, perceived risk and website information have a strong impact on purchase decisions.…”
Section: Relationship Between Opr and Opimentioning
confidence: 99%
“…In case of CE research, word-of-mouth positively influences loyalty and product recommendation (Babin, Lee, Kim, & Griffin, 2005;Cetin & Dincer, 2014) With the evolution of online social media, modern customers are now more vocal in expressing their expectations and experiences about product and service through various online communication channels (Verma, 2014). Consequently, word-of-mouth has evolved into eWOM (Hennig-Thurau, Gwinner, Walsh, & Gremler, 2004) which online shoppers use for information search, product comparison and opinion formation (Roy, Datta, & Basu, 2017) while for marketers it is a potent tool for persuasion (Alboqami et al, 2015). eWOM is defined as 'any positive or negative statement made by potential, actual or former customers about a product or company, which is made available to a multitude of people and institutions via the Internet' (Hennig-Thurau et al, 2004).…”
Section: Cognitive Experience Online Shopping (Ceos)mentioning
confidence: 99%
“…eWOM has been regarded as the most credible source of product information, and potential customers often pay attention to eWOM during purchase decisions [5]. Positive eWOM significantly increase sales [6,7], brand equity [8], and company's reputation [9]; whereas, negative eWOM significantly lowers purchase intentions and brand trust [10]. eWOM is more influential as compared to conventional interpersonal interactions because of high virality, reliability, and anonymity [11].…”
Section: Introductionmentioning
confidence: 99%